2019
DOI: 10.1039/c9ta07416c
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrically recombined nanofibers in a high-selectivity membrane for cation separation in high temperature and organic solvent

Abstract: Symmetrically recombining poly(p-phenylene terephthalamide) nanofibers and 2,5-diaminobenzenesulfonic acid based on amide hydrolysis and amide condensation reaction for ion separation in high temperature and organic solvent environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Zhao et al reported a KANF-based CEM with a high performance for ion separation in ED with a maximum desalination efficiency of 99.7% after 220 min for Na 2 SO 4 and significant selectivity for monovalent cations. Moreover, KANF-based membranes demonstrate exceptional desalination at high temperatures (as high as 100 • C) and organic solvent/aqueous environments (as high as 80% acetone solution) [55]. Additionally, some studies reported the application of IEX-NFs as a composite along with BPMs.…”
Section: Membrane Separationmentioning
confidence: 99%
“…Zhao et al reported a KANF-based CEM with a high performance for ion separation in ED with a maximum desalination efficiency of 99.7% after 220 min for Na 2 SO 4 and significant selectivity for monovalent cations. Moreover, KANF-based membranes demonstrate exceptional desalination at high temperatures (as high as 100 • C) and organic solvent/aqueous environments (as high as 80% acetone solution) [55]. Additionally, some studies reported the application of IEX-NFs as a composite along with BPMs.…”
Section: Membrane Separationmentioning
confidence: 99%
“…Furthermore, there are many valuable and essential ions in the hospital wastewater, which could be selectively separated or extracted for reuse such as Xe [101]. However, the coexistence of chemically similar ions in wastewater severely limits the extraction of these valuable ions [102,103]. Currently, the inevitability of environmental pollution and low-efficiency implementation of the traditional methodologies, including calcina- tion, adsorption, precipitation, and salting, limit the use of these methods in wastewater treatment [104].…”
Section: Radioactive Elements and Ionic Pollutantsmentioning
confidence: 99%
“…However, the use of traditional polymer membranes is limited to a specific temperature range and solvent selection 9 . In recent years, in order to meet the needs of complex industrial applications, researchers are committed to high performance polymer membrane materials, especially those with heat resistance and chemical corrosion resistance 10–13 …”
Section: Introductionmentioning
confidence: 99%